Confronting trade‐offs and interactive effects in the choice of policy focus: Specialized versus comprehensive private governance. Issue 1 (26th August 2013) - Auld, Graeme
Abstract In setting standards for responsible business practices, certification programs create issue boundaries delineated by the focus of their standards. These issue boundaries may impede action on certain causes of problems (i.e. problem interactive effects) or lead to policy actions that affect other governance initiatives (i.e. policy interactive effects). When these interactions are extensive, programs confront trade‐offs: develop as a comprehensive program (i.e. have a broad policy focus) and take on higher internal administrative costs, or develop as a specialized program (i.e. have a narrow policy focus) and undertake to develop mechanisms to facilitate across‐program coordination. This paper explores these trade‐offs. It examines the origins of the different policy foci of coffee, forest, and fisheries certification programs, and identifies five strategies that programs are currently using to manage policy and/or problem interactive effects. Then, informed by research in public administration and international relations, it details additional approaches for improving issue‐boundary management.